Brave New Teachers: Doing Social Justice Work in Neo-liberal Times - Barbara Anne Pollard (University of Windsor, 2015)
The authors of Brave New Teachers adopt a critical-democratic lens to analyze how neoliberal educational agendas have impacted the ability of progressive teachers to cultivate equitable and inclusive classrooms. The book is based on a longitudinal study that documents the self-reported teaching experiences of a group of teachers who graduated from the Urban Diversity Program at York University. Brave New Teachers explores how the current context of Canadian schooling has been shaped by neoliberalism. Within this paradigm, the authors thematically emphasize how the standardized testing and accountability movement, as well as the top-down imposition of curriculum standards, circumscribe the efforts of courageous teachers who work diligently on creating anti-oppressive curriculums and school environments. The tension that exists when these teachers feel pressured to conform to higher top-down authorities is documented throughout the` book.